The Role of Shared Leadership and Team Cohesion in Shaping the Effectiveness of Multidisciplinary Research Teams in Indonesia - Rani Intan (Publikasi Indonesia, 2025)
Cross-disciplinary scientific collaboration and expertise continue to be encouraged to increase the productivity of higher-quality research and produce reputable scientific publications. This effort is important considering that collaboration and research output are still among the benchmarks of scientific progress in Indonesia; until now, they are considered not to have reached an optimal level. One of the efforts to improve the quality and productivity of research is through the formation of an effective research team. This study aims to analyze the determinants of team effectiveness formation, consisting of shared leadership and team cohesion. The study used a quantitative approach involving 240 research respondents from various research teams in universities and research institutions in Indonesia. The research model was developed through three main theories: Human Resource Management and Group Dynamics as grand theories; Organizational Behavior as a middle theory; and the IPO Framework as an applied theory. The results of the analysis using PLS-SEM show that team cohesion has a direct, positive, and significant influence on team effectiveness, while shared leadership has a positive and significant influence on team effectiveness both directly and indirectly through team cohesion. Team cohesion has proven to be a positive mediator and has a significant influence in bridging the effect of shared leadership on team effectiveness. This means that shared leadership can increase team effectiveness if all team members are cohesive.